Ontology based document annotation: trends and open research problems. (24th January 2006) - Corcho, Oscar
Metadata is used to describe documents and applications, improving information seeking and retrieval and its understanding and use. Metadata can be expressed in a wide variety of vocabularies and languages, and can be created and maintained with a variety of tools. Ontology based annotation refers to the process of creating metadata using ontologies as their vocabularies. We present similarities and differences with respect to other approaches for metadata creation, and describe languages and tools that can be used to implement these annotations.